Dark Patterns: Towards a Socio-technical Approach - Baroni, Luiz Adolpho; Puska, Alisson Andrey; Salgado, Luciana Cardoso de Castro; Pereira, Roberto (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2021)
The term Dark Pattern has been used to define design patterns intentionally created to deceive users or favor the interests of parties other than users. Dark Patterns present socio-technical characteristics as something that happens when humans interact with technical artifacts in a given environment, causing annoyance, frustration, anger, and other emotions in users. Comprehending Dark Patterns require us to look at them from different perspectives, in a multifocal way, considering social and technical aspects in an intertwined way. In this paper, we apply the Semiotic Framework to analyze and discuss Dark Patterns from a socio-technical perspective. We use a popular Dark Pattern called Roach Motel to exemplify our discussion, unraveling it with the Semiotic Framework. Results show the complexity of the topic and exemplify the potential of a socio-technical approach to understand, characterize and advance our knowledge on it.